Calcium/Calmodulin Dependent Protein Kinase Kinase 2 Regulates the Expansion of Tumor-Induced Myeloid-Derived Suppressor Cells - Huang, Wei; Liu, Yaping; Luz, Anthony; Berrong, Mark; Meyer, Joel N.; Zou, Yujing; Swann, Excel; Sundaramoorthy, Pasupathi; Kang, Yubin; Jauhari, Shekeab; Lento, William; Chao, Nelson; et al. (Frontiers in Immunology, 2021)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous group of cells, which can suppress the immune response, promote tumor progression and impair the efficacy of immunotherapies. Consequently, the pharmacological targeting of MDSC is emerging as a new immunotherapeutic strategy to stimulate the natural anti-tumor immune response and potentiate the efficacy of immunotherapies. Herein, we leveraged genetically modified models and a small molecule inhibitor to validate Calcium-Calmodulin Kinase Kinase 2 (CaMKK2) as a druggable target to control MDSC accumulation in tumor-bearing mice. The results indicated that deletion of CaMKK2 in the host attenuated the growth of engrafted tumor cells, and this phenomenon was associated with increased antitumor T cell response and decreased accumulation of MDSC. The adoptive transfer of MDSC was sufficient to restore the ability of the tumor to grow in Camkk2-/- mice, confirming the key role of MDSC in the mechanism of tumor rejection. In vitro studies indicated that blocking of CaMKK2 is sufficient to impair the yield of MDSC. Surprisingly, MDSC generated from Camkk2-/- bone marrow cells also showed a higher ability to terminally differentiate toward more immunogenic cell types (e.g inflammatory macrophages and dendritic cells) compared to wild type (WT). Higher intracellular levels of reactive oxygen species (ROS) accumulated in Camkk2-/- MDSC, increasing their susceptibility to apoptosis and promoting their terminal differentiation toward more mature myeloid cells. Mechanistic studies indicated that AMP-activated protein kinase (AMPK), which is a known CaMKK2 proximal target controlling the oxidative stress response, fine-tunes ROS accumulation in MDSC. Accordingly, failure to activate the CaMKK2-AMPK axis can account for the elevated ROS levels in Camkk2-/- MDSC. These results highlight CaMKK2 as an important regulator of the MDSC lifecycle, identifying this kinase as a new druggable target to restrain MDSC expansion and enhance the efficacy of anti-tumor immunotherapy.